How Does Variation in the Body Composition of Both Stimuli and Participant Modulate Self-Estimates of Men’s Body Size? - Groves, Vicki; Cornelissen, Piers; McCarty, Kristofor; Mohamed, Sophie; Maalin, Nadia; Tovée, Martin James; Cornelissen, Katri (Frontiers in Psychiatry, 2019)
When measured in units of body mass index (BMI), how much variation in men’s self-estimates of body size is caused by: (i) variation in participants’ body composition and (ii) variation in the apparent muscle mass and muscle tone of the stimuli being judged? To address this, we generated nine sets of male CGI bodies representing low, mid and high muscle mass rendered at low, mid and high muscle tone, from 18.75-40 BMIhse units. BMIhse units in this study are estimates of BMI derived from calibration equations predicting BMI from waist and hip circumference, age, sex, height and ethnicity in the Health Survey for England databases. Forty-five healthy adult men estimated their body size using a yes-no paradigm for each combination of muscle mass/tone. We also measured participants’ body composition with Harpenden callipers and their body concerns with psychometric questionnaires. We show that stimulus variation in apparent muscle mass/tone can introduce differences up to 2.5 BMIhse units in men’s self-estimates of body size. Moreover, men with the same actual BMI, but different body composition, showed up to 5-7 BMIhse unit differences in self-estimates of body size. In the face of such large errors, we advocate that such judgements in men should be made instead by simultaneously manipulating both the adiposity and the muscle mass of stimuli which are appropriately calibrated for body composition, so that the participant can match the body size and shape they believe themselves to have to the stimulus they see.